Design Business Offline and Online Based on Website of Pikyeum SME in Bandung - Dinda Syabila Elfani; Endang Chumaidiyah; Sinta Aryani (International Journal of Innovation in Enterprise System, 2022)
Pikyeum SME created a new business idea to connect sellers and consumers, introduce products,and place online purchases. By creating a website, Pikyeum SME makes it easy for consumersthroughout Indonesia to find Peuyeum chips. This case study was conducted in Pikyeum SME,located in Lot Leuwidulang No. C 02, Sub-district Pameungpeuk, Bandung, Indonesia. Datacollection and analysis were conducted qualitatively and quantitatively. The purpose of thisresearch is to measure the demand, design technical and operational aspects, design a websitebased application, measure the product's financial feasibility, and measure the sensitivity level ofPikyeum food products offline and online sales. Survey data were analyzed using corrected itemtotal correlation as a validity testing technique and Cronbach's Alpha as a reliability testingtechnique with the aid of the SPSS program. Based on this research, Net Present Value (NPV) isIDR 167.006.461, Interest Rate of Return (IRR) at 36,70%, and Payback Period at 3,4 years. It canbe concluded that Pikyeum SME is feasible to run because NPV > 0, payback period < asseteconomic life, and IRR > MARR. The increase of raw materials and packaging costs shouldn’t bemore than 36,76%. Meanwhile, the increase of labor cost shouldn’t be more than 23,51%. Thedemand decreases shouldn’t be more than 15,63% and selling prices shouldn’t exceed 11,34%.